2020
DOI: 10.1093/infdis/jiaa447
|View full text |Cite
|
Sign up to set email alerts
|

Continued In-Hospital Angiotensin-Converting Enzyme Inhibitor and Angiotensin II Receptor Blocker Use in Hypertensive COVID-19 Patients Is Associated With Positive Clinical Outcome

Abstract: This study investigated continued and discontinued use of angiotensin-converting enzyme inhibitors (ACEi) or angiotensin II receptor blockers (ARB) during hospitalization of 614 hypertensive laboratory-confirmed COVID-19 patients. Demographics, comorbidities, vital signs, and laboratory data and ACEi/ARB usage were analyzed. To account for confounders, patients were sub-stratified by whether they developed hypotension and acute kidney injury (AKI) during the index hospitalization. Mortality (22% vs 17%, p&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
107
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 32 publications
(31 reference statements)
8
107
1
Order By: Relevance
“…[56][57][58][59][60] Some recent studies support this view, and populationbased reports revealed that the use of ACEI and ARB inhibitors in patients with COVID-19 does not aggravate the severity of the disease, increase the risk of infection, improve prognosis, or reduce mortality. [61][62][63][64][65][66] In addition, a systematic review and meta-analysis of related research has reconfirmed this thesis. [67][68][69][70][71] Given that hypertension and CVD can increase the severity of the disease, dividing patients without hypertensive and CVD into a non-ACEI/ARB group may underestimate the favorable effects of ACEI/ARB drugs on affected patients.…”
Section: Sars-cov-2mentioning
confidence: 61%
“…[56][57][58][59][60] Some recent studies support this view, and populationbased reports revealed that the use of ACEI and ARB inhibitors in patients with COVID-19 does not aggravate the severity of the disease, increase the risk of infection, improve prognosis, or reduce mortality. [61][62][63][64][65][66] In addition, a systematic review and meta-analysis of related research has reconfirmed this thesis. [67][68][69][70][71] Given that hypertension and CVD can increase the severity of the disease, dividing patients without hypertensive and CVD into a non-ACEI/ARB group may underestimate the favorable effects of ACEI/ARB drugs on affected patients.…”
Section: Sars-cov-2mentioning
confidence: 61%
“…The spatiotemporal characteristics on pCXR of COVID-19 infection and its relation to clinical outcomes are unknown. Future endeavors could include developing AI algorithms to stage severity, and predict progression, treatment response, recurrence, and survival, to inform and advise risk management and resource allocation associated with the COVID-19 pandemic, with inclusion of clinical variables in predictive models (Lam et al, 2020;Zhao et al, 2020;Zhu et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Richardson et al showed an increasing trend in mortality in ACE-I and ARB users compared with nonusers, with approximately 50% of the patients discontinuing the drug in the course of hospitalization 22 . Lam et al compared COVID-19 patients who continued and discontinued ACE-I or ARB after excluding cases of hypotension and AKI 35 . Patients who could continue ACE-I or ARB demonstrated lower mortality and intensive care unit admission rates.…”
Section: Discussionmentioning
confidence: 99%